Penggunaan Bahasa Baku Dalam Penulsan Karya Ilmiah - Wulandari, Dinda Riris; Silvia, Cindy; Budiman, Budiman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This essay outlines the factors that should be taken into account when students employ standard language in their scientific writing. The range of raw materials is reflected in the languages used in scientific papers. In scientific communities, standard language is the norm. In writing, there are requirements that must be met in order to be compliant with Ejaan Yang Disempurnakan (EYD). The usage of uppercase and oblique letters, foreign word absorption, inappropriate word placement, cutting words, and superfluous words are all things to pay attention to words.tandart language, scientific paper. Key word: s